FAKTOR-FAKTOR YANG MEMPENGARUHI RISIKO SISTEMATIS PERUSAHAAN INDEX LQ-45 - Intan Adi Irana; Damayanti Damayanti (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2023)
This study aims to prove the effect of leverage, liquidity, and asset growth on systematic risk in companies that are members of the LQ-45 index on the Indonesia Stock Exchange. The population used in this study is companies that are members of the LQ-45 index on the Indonesia Stock Exchange in 2017-2021. The sample selection technique uses purposive sampling. Data analysis technique using multiple linear regression analysis. The results of this study indicate that leverage has a significant positive effect on systematic risk, liquidity has an insignificant positive effect and asset growth has an insignificant negative effect on systematic risk of companies listed on the LQ-45 index on the Indonesia Stock Exchange. The value of Adjusted R² is 0.210, which means that 21% of the variation in the systematic risk of companies listed on the LQ-45 index on the Indonesia Stock Exchange can be explained by the three independent variables, namely leverage, liquidity and asset growth. While the remaining 79% is explained by other variables not examined in this study.